Universiti Utara Malaysia - Malaysia, Focus (Focus Malaysia, 2013)
Universiti Utara Malaysia (UUM) vice-chancellor Prof Datuk Dr Mohamed Mustafa Ishak (left), former Asean secretary-general Dr Surin Pitsuwan (centre) and UUM faculty member and conference co-director Dr Kamaruddin Abdulsomad attend the International Conference on Innovation and Sustainability, held by the university on April 3.